Water-based silica coatings: An environmentally friendly process on an industrial scale of single-layer anti-reflective coatings for large substrates. Issue 3 (1st February 2022) - Kócs, Lenke; Jilavi, Mohammad H.; Beckelmann, Dirk; Schäfer, Bruno; May, Alexander; Koch, Marcus; de Oliveira, Peter W.
Abstract: A new water-based silica sol was developed to provide single-layer anti-reflective (AR) coatings. The combination of nanoparticle-based aqueous coating and wiping-coating method facilitated to reduce the solvent waste. The wiping-coating process requires only 35 ml sol to cover a large glass substrate (80 × 160 cm). Samples coated on one side show an improvement in light transmission in the visible range: the maximum transmission is 95.12 ± 0.33% on float glass and 92.48 ± 0.25% on display glass. This is an excellent performance compared to the extra 99.04% maximum transmission of samples coated on both sides. The layer thickness distribution defined by the ellipsometry of 98 samples (10 × 10 cm) shows homogeneity (77.4 ± 2.2 nm) over the total area. Homogeneous films with good surface wetting were applied on glass, polycarbonate (PC), and acrylic glass (PMMA). The cured layers were successfully tested against dry heat, damp heat (40 °C/98% RH), and climatic change (−40 °C–40 °C/98% RH) on all three substrate materials. No delamination from the substrate was observed. The changes in the minimum reflection after exposure to damp heat and climatic change were minimal (ΔR = ±0.6%) in the wavelength range of 400–1000 nm. The addition of Levasil nanoparticles into the water-based silica sol improved coating hardness on glass sheets up to 3H pencil hardness without significant loss in transmission.